The development of organizational memory information system in academic setting - Mohmad Hassim, Yana Mazwin; Mokhtar, Salimah; Hamid, Suraya (2006)
This study is concerned with proposing a suitable organizational memory framework for Faculty Memory Information System and the development of Faculty Memory Information System (FMIS) prototype for the Faculty of Computer Science & Information Technology, UM.The framework portrays interaction between components that support the institution memory and the information system components that support the effort to captures and preserves the institutional knowledge. Finally, based on the proposed framework, computational support is proposed to be web-based prototype to enable usage in intranet and Internet environment.A web-based environment would facilitate faculty members to utilize the prototype without limiting themselves to the physical presence at the faculty.